PERBANDINGAN EFISIENSI WAKTU, BIAYA, DAN SUMBER DAYA MANUSIA ANTARA METODE BUILDING INFORMATION MODELLING (BIM) DAN KONVENSIONAL (STUDI KASUS: PERENCANAAN GEDUNG 20 LANTAI) - Chinthia Ayu Berlian P.; Randy Putranto Adhi; Arif Hidayat; Hari Nugroho (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2016)
The construction development which grows fast in Indonesia is causing needs of supporting technology that give more efficiency yet it also has to be more effective. Technological developments in the field of construction is giving a system called Building Information Modelling (BIM) as a result. Before BIM, we already aware of AutoCAD, SAP, Ms.Project that have been used for project planning, the use of these softwares take a lot of time because they can’t be integrated, so it need more cost, human resources and time to for a project planning. BIM encourage the exchange between different diciplines, so that this exchange process could get faster and affecting the costruction itself in a good way. Currently in Indonesia, there are a lot of construction workers who haven’t use BIM technology, even acknowledge about the benefits it gave, while in fact, BIM have so many excellences compared to the common technology that have been used. Thus, writers do this research to acknowledge about comparison between BIM and conventional methods. Writers are using three methods, they are questionnaires, interviews and a case study, to acknowledge about the performance of BIM. With case studies planning of 20 storey building made comparisons between the efficiency of conventional methods with BIM concept in need of time, human resources and costs for project planning.This study concluded that the use of the application with the concept of BIM can accelerate project planning time by ± 50%, BIM reduces the human resources needs by 26,66%, and saving personnel costs to 52,25% as compared to using conventional method.